(3fMh EjLGO bGfhfjI edGFeI dHQeLjGJ GdMGSH(B:s (3OQGSI ebGQfI(B/s - (3EjgGH YHO GdefYe eMeO QVhGfs; (3SejMI eUWai GdbdjhHjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2016)
(3JfGhd GdHMK OQGSI eOi edGAeI MeGjI GdHQeLjGJ HGdCfXeI GdeJHYI dMeGjJgG Mb GdeDda, HQGAI GdGNJQGY, GdeYdheGJ ZjQ GdeaUM YfgG, MjK OGQJ ETcGdjI GdHMK Mhd JMOjO GdWHjYI GdbGfhfjI ddHQeLjGJ cNWhI CSGSjI fMh GdJYQa Ydi GdCSdhH GdCeKd dMeGjJgG(B. (3haj SHjd JMbjb Pdc, GSJYQV GdHMK cGaI GdLhGfH GdeQJHWI HJdc GdCfXeI, hbGe HEfRGdgG Ydi GdHQeLjGJ, hGfJgi Edi YOe edGAeI MeGjJgG hab Cj ef Jdc GdCfXeI; fXkQG dCf GdHQeLjGJ ef GdeUfaGJ GdacQjI PGJ Jdc GdWHjYI GdNGUI, hGdJj JSJdRe GSJMOGK fXGe MeGjI NGU heJejR jJdGAe eY GdWHjYI(B. (3hGfJgL GdHMK efgL GdOQGSI GdebGQfI, MjK bGQf Hjf GdbGfhf GdeUQj hcd ef GdbGfhf GdCeQjcj, hGdbGfhf GdaQfSj, hGdJhLjg GdChQHj, hGJaGbjI GdJQjHS, hGSJYGf HGdYOjO ef GdJWHjbGJ GdbVGFjI GdegeI aj GdbVGA GdCeQjcj(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI(B- (3cdjI GdMbhb(B- (3bSe GdbGfhf GdYGe, (B2016s
(3HHdjhLQGajG(B: (3UaMGJ (B679-706s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3HQeLjGJ GdMGShHs; (3Mb GdeDdas; (3HQGAGJ GdGNJQGYs; (3MeGjI GdeYdheGJs; (3GdeUfaGJ GdHQeLjIs; (3GdMb GdeGdjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes